Second Five Year Plan Madras State Chingleput District - Planning Commission (Planning Commission, 1956)
In accordance with the instructions contained in G.O. Ms. No. 1090, Public (Planning and Development), dated 30th March 1955, the whole of the Chinglcput district excluding the three Municipalities, fifteen Major Panchayats and one Cantonment area was divided into 23 Planning Areas including four Development Blocks and again into 777 Development Units. the Municipalities, Major Panchayats and the Cantonment Board have prepared plans of their own. Appendix J shows the Planning Areas with their population and Appendix II gives an abstract of the Planning Areas and the Village Development Units comprised in each taluk.
Madras State